THE INFLUENCE OF WORK BEHAVIOR ON EMPLOYEE PERFORMANCE THROUGH THE WORK ENVIRONMENT AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY OF LABUHAN BATU REGENCY - Muhammad Bagus Nugraha; Salman Faris; Agung Sahbana (Jurnal Ekonomi Bisnis Manajemen Prima, 2026)
The decline in the quality of a bureaucracy is often caused by employees who are less than optimal in carrying out their duties. Therefore, this study will examine the influence of work behavior on employee performance through the work environment at the Regional Financial and Asset Management Agency (BPPA) of Labuhanbatu Regency. Data collection in this study used quantitative methods, and analysis utilized Structural Equation Modeling (SEM). The research population was all employees at the Regional Financial and Asset Management Agency of Labuhanbatu Regency and agencies related to the institution. Data collection and collection involved field observation and questionnaires. The study concluded that work behavior positively influences the work environment. Work behavior also positively influences employee performance. Furthermore, the work environment positively influences employee performance. Finally, work behavior positively influences employee performance through the work environment at the Regional Financial and Asset Management Agency (BPPA) of Labuhan batu Regency.